2015
DOI: 10.1166/asl.2015.6243
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality: A Case Study Using SERVQUAL Model

Abstract: Resumo Nas últimas duas décadas, pesquisadores em ciência da informação têm investigado o valor dos serviços em bibliotecas de acordo com as percepções, expectativas e necessidades dos usuários. No Brasil, a avaliação de bibliotecas universitárias tem desempenhado um importante papel nas avaliações das instituições de educação superior e dos cursos de graduação. Neste contexto, é essencial que exista um procedimento eficiente para monitorar a qualidade dos serviços prestados por bibliotecas universitárias. Vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…4 Colmenares y Saavedra (2007) afirman que el SERVQUAL es una referencia obligada en el estudio de la calidad de los servicios. Siguiendo su metodología se han realizado diversas investigaciones en el mundo y en Iberoamérica en diversos ámbitos, entre los que aparecen los comedores universitarios (Cevallos, 2015); el servicio postal (Roslan et al, 2015); el transporte público (Valenzo et al, 2019); y los centros de acondicionamiento físico (Peitzika et al, 2020). Respecto a la salud pública figuran, entre otros, los trabajos de Cabello y Chirinos (2012), Pedraza et al (2014), Zapata (2014), Pedraza et al (2015), Henao et al (2018), y Teshnizi et al (2018.…”
Section: El Modelo Service Quality (Servqual)unclassified
“…4 Colmenares y Saavedra (2007) afirman que el SERVQUAL es una referencia obligada en el estudio de la calidad de los servicios. Siguiendo su metodología se han realizado diversas investigaciones en el mundo y en Iberoamérica en diversos ámbitos, entre los que aparecen los comedores universitarios (Cevallos, 2015); el servicio postal (Roslan et al, 2015); el transporte público (Valenzo et al, 2019); y los centros de acondicionamiento físico (Peitzika et al, 2020). Respecto a la salud pública figuran, entre otros, los trabajos de Cabello y Chirinos (2012), Pedraza et al (2014), Zapata (2014), Pedraza et al (2015), Henao et al (2018), y Teshnizi et al (2018.…”
Section: El Modelo Service Quality (Servqual)unclassified
“…SERVQUAL is built on this paradigm (Parasuraman et al, 1991a, and it has found numerous applications as a service quality measure (Babakus & Boller, 1992;Brysland & Curry, 2001;Donnelly, Mike, & Shiu et al, 1999;Donnelly et al, 2006;Donnelly, Wisniewski, Dalrymple & Curry, 1995;Dyke et al, 1999;Lam & Woo, 1997;Parasuraman et al, 1991bWeekes, Scott, & Tidwell, 1996;Wisniewski, 2001aWisniewski, , 2001b. Moreover, it continues to be very popular as a service quality measure across many cultures (Aghamolaei et al, 2014;Musah et al, 2015;Ogunnowo, Olufunlayo, & Sule, 2015;Roslan, Nor, & Wahab, 2015). The instrument has been described as the most commonly used tool for measuring service quality.…”
Section: Measuring Service Qualitymentioning
confidence: 99%